(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This research aims to identify the potential of aromatic ginger to develop sustainable herbal plants for feed additives in East Java Province, Indonesia. The first research stage on aromatic ginger production conditions used a quantitative approach. The research method used was a literature study. Data collection used secondary data. A quantitative descriptive data analysis was in formal and informal form. The second stage was to identify aromatic ginger in several districts in East Java using a qualitative approach. The research method used was observation. The subjects were several districts in East Java. The data was the physical appearance of aromatic ginger in several districts in East Java. Qualitative descriptive analysis was used for the physical appearance of aromatic ginger. The third stage was the marketing conditions of aromatic ginger in East Java Province. The survey method was used to obtain marketing data for aromatic ginger in several districts in East Java. Data analysis was quantitative and qualitative descriptive analysis. The results obtained from research were aromatic ginger production in East Java varies between districts. The major producer of aromatic ginger in East Java was Pacitan District. Aromatic ginger from Lumajang District displays the best physical characteristics. The physical characteristics of aromatic ginger from Lumajang were superior in almost all parameters, namely yellow color, distinctive pungent aroma, clean appearance, spicy aromatic ginger taste, large size, and good freshness level. The cheapest price comes from aromatic ginger production in Malang District. The aromatic ginger from the Probolinggo District was the most expensive price.